KUALITAS PELAYANAN DI PT LAKSMANA MULIA WISATA PEKANBARU - Sari, Syafira Permata; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The tourism industry in Pekanbaru is growing rapidly along with the increasing public demand for religious tourism services such as Umrah and halal tourism. PT Laksmana Mulia Wisata as a travel agency that was just established in 2022 faces challenges in meeting consumer expectations for service quality. This study aims to analyze customer perceptions of the company's service quality based on five dimensions of SERVQUAL, namely tangibles, reliability, responsiveness, assurance, and empathy. The research method used is descriptive quantitative, with data obtained by distributing questionnaires to 75 service user respondents. The results of the analysis show that in general customers assess the quality of PT Laksmana Mulia Wisata's services to be in the good category, especially in the dimensions of empathy and assurance which indicate a high level of satisfaction. However, weaknesses were still found in the physical and responsive aspects, especially related to limited human resources. Based on these findings, it can be concluded that the company needs to improve physical facilities and service responsiveness so that customer satisfaction is optimal. This study is expected to be the basis for evaluation and service improvement strategies, as well as provide academic contributions to the development of service quality theory in the religious tourism sector. Keywords: Service Quality, SERVQUAL, Tourism, Umrah, PT Laksmana Mulia Wisata.